Ultra-Processed Food Consumption and The Risk of Obesity: A Systematic Literature Review - Rova Maulina Dewi (Universitas Airlangga, 2026)
Background: Obesity has become a major public health issue worldwide. One factor often associated with this increase is the change in eating habits, especially the growing intake of Ultra-Processed Foods (UPFs). These foods usually contain high levels of calories, added sugar, saturated fat, and sodium but only small amounts of fiber and essential micronutrients. Objectives: This study aimed to examine the relationship between ultra-processed food consumption and obesity risk through a systematic review of recent scientific evidence. Methods: This review followed the PRISMA Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Relevant articles were searched in the Scopus database using keywords related to ultra-processed foods, the NOVA classification, obesity, overweight, and Body Mass Index (BMI). Studies published from 2021 to 2026 were screened according to predetermined inclusion and exclusion criteria. In total, 4,258 records were identified in the initial stage, and 37 studies were ultimately considered eligible for inclusion. The selected studies were qualitatively analyzed to identify common patterns in the relationship between UPF consumption and obesity-related outcomes. Results: Most of the reviewed studies showed that a higher consumption of ultra-processed foods was associated with a higher BMI, greater body weight, and increased adiposity. Similar findings have been reported across various population groups, including children, adolescents, and adults. Regular intake of UPFs is generally associated with a higher risk of being overweight or obese. This may be explained by the nutritional profile of these foods, which tends to be high in calories, sugar, fat, and sodium, thereby encouraging excess energy intake and metabolic imbalances. Conclusion: The evidence consistently suggests that a high consumption of ultra-processed foods is associated with an increased risk of obesity.